Standard-dose versus high-dose conformal radiotherapy with concurrent and consolidation carboplatin plus paclitaxel with or without cetuximab for patients with stage IIIA or IIIB non-small-cell lung cancer (RTOG 0617): a randomised, two-by-two factorial phase 3 study. Issue 2 (February 2015) - Bradley, Jeffrey D; Paulus, Rebecca; Komaki, Ritsuko; Masters, Gregory; Blumenschein, George; Schild, Steven; Bogart, Jeffrey; Hu, Chen; Forster, Kenneth; Magliocco, Anthony; Kavadi, Vivek; Garces, Yolanda I; et al.
Summary Background We aimed to compare overall survival after standard-dose versus high-dose conformal radiotherapy with concurrent chemotherapy and the addition of cetuximab to concurrent chemoradiation for patients with inoperable stage III non-small-cell lung cancer. Methods In this open-label randomised, two-by-two factorial phase 3 study in 185 institutions in the USA and Canada, we enrolled patients (aged ≥18 years) with unresectable stage III non-small-cell lung cancer, a Zubrod performance status of 0–1, adequate pulmonary function, and no evidence of supraclavicular or contralateral hilar adenopathy. We randomly assigned (1:1:1:1) patients to receive either 60 Gy (standard dose), 74 Gy (high dose), 60 Gy plus cetuximab, or 74 Gy plus cetuximab. All patients also received concurrent chemotherapy with 45 mg/m2 paclitaxel and carboplatin once a week (AUC 2); 2 weeks after chemoradiation, two cycles of consolidation chemotherapy separated by 3 weeks were given consisting of paclitaxel (200 mg/m2) and carboplatin (AUC 6). Randomisation was done with permuted block randomisation methods, stratified by radiotherapy technique, Zubrod performance status, use of PET during staging, and histology; treatment group assignments were not masked. Radiation dose was prescribed to the planning target volume and was given in 2 Gy daily fractions with either intensity-modulated radiation therapy or three-dimensional conformal radiation therapy. The use of four-dimensional CT and image-guided radiation therapy were encouraged but not necessary. For patients assigned to receive cetuximab, 400 mg/m2 cetuximab was given on day 1 followed by weekly doses of 250 mg/m2, and was continued through consolidation therapy. The primary endpoint was overall survival. All analyses were done by modified intention-to-treat. The study is registered with ClinicalTrials.gov, number NCT00533949. Findings Between Nov 27, 2007, and Nov 22, 2011, 166 patients were randomly assigned to receive standard-dose chemoradiotherapy, 121 to high-dose chemoradiotherapy, 147 to standard-dose chemoradiotherapy and cetuximab, and 110 to high-dose chemoradiotherapy and cetuximab. Median follow-up for the radiotherapy comparison was 22·9 months (IQR 27·5–33·3). Median overall survival was 28·7 months (95% CI 24·1–36·9) for patients who received standard-dose radiotherapy and 20·3 months (17·7–25·0) for those who received high-dose radiotherapy (hazard ratio [HR] 1·38, 95% CI 1·09–1·76; p=0·004). Median follow-up for the cetuximab comparison was 21·3 months (IQR 23·5–29·8). Median overall survival in patients who received cetuximab was 25·0 months (95% CI 20·2–30·5) compared with 24·0 months (19·8–28·6) in those who did not (HR 1·07, 95% CI 0·84–1·35; p=0·29). Both the radiation-dose and cetuximab results crossed protocol-specified futility boundaries. We recorded no statistical differences in grade 3 or worse toxic effects between radiotherapy groups. By contrast, the use of cetuximab was associated with a higher rate of grade 3 or worse toxic effects (205 [86%] of 237 vs 160 [70%] of 228 patients; p<0·0001). There were more treatment-related deaths in the high-dose chemoradiotherapy and cetuximab groups (radiotherapy comparison: eight vs three patients; cetuximab comparison: ten vs five patients). There were no differences in severe pulmonary events between treatment groups. Severe oesophagitis was more common in patients who received high-dose chemoradiotherapy than in those who received standard-dose treatment (43 [21%] of 207 patients vs 16 [7%] of 217 patients; p<0·0001). Interpretation 74 Gy radiation given in 2 Gy fractions with concurrent chemotherapy was not better than 60 Gy plus concurrent chemotherapy for patients with stage III non-small-cell lung cancer, and might be potentially harmful. Addition of cetuximab to concurrent chemoradiation and consolidation treatment provided no benefit in overall survival for these patients. Funding National Cancer Institute and Bristol-Myers Squibb.